Clinical detection of neurodegenerative blood biomarkers using graphene immunosensor. (30th October 2020) - Li, Bing; Tan, Haijie; Jenkins, David; Srinivasa Raghavan, Vikram; Rosa, Bruno Gil; Güder, Firat; Pan, Genhua; Yeatman, Eric; Sharp, David J.
Abstract: Accurate detection of blood biomarkers related to neurodegenerative diseases could provide a shortcut to identifying early stage patients before the onset of symptoms. The specificity, selectivity and operational requirements of the current technologies, however, preclude their use in the primary clinical setting for early detection. Graphene, an emerging 2D nanomaterial, is a promising candidate for biosensing which has the potential to meet the performance requirements and enable cost-effective, portable and rapid diagnosis. In this review, we compare graphene-based immunosensing technologies with conventional enzyme-linked immunosorbent assays and cutting-edge single molecule array techniques for the detection of blood-based neurodegenerative biomarkers. We cover the progress in electrical, electrochemical and optical graphene-based immunosensors and outline the barriers that slow or prevent the adoption of this emerging technology in primary clinical settings. We also highlight the possible solutions to overcome these barriers with an outlook on the future of the promising, graphene immunosensor technology. Graphical abstract: Image 1 Highlights: Comparisons between gold standard laboratory methods and graphene immunosensor. State-of-art of graphene immunosensors for the neurodegenerative biomarker detection. Bottlenecks of graphene immunosensors in clinical adoption. Further development strategies for clinical adoption of graphene immunosensors.